2009
DOI: 10.1111/j.1460-9568.2009.06995.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of colour‐selective activity in the monkey inferior temporal cortex revealed by functional magnetic resonance imaging

Abstract: Previous electrophysiological, neuroimaging and lesion studies have suggested that the anterior part of the monkey inferior temporal (IT) cortex, or area TE, plays an important role in colour processing. However, little is known about how colour information is distributed in these cortical regions. Here, we explored the distribution of colour‐selective activity in alert macaque monkeys using functional magnetic resonance imaging (fMRI) with two types of stimuli: a multicoloured (‘Mondrian’) pattern and an isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 68 publications
6
37
1
Order By: Relevance
“…Each monkey was extensively trained to perform a fixation task in a mock scanner environment. Detailed descriptions of the surgery and training are provided previously (Harada et al, 2009;Okazawa et al, 2012). All experimental procedures were in accordance with NIH guidelines and were approved by the Animal Experiment Committee of Okazaki National Research Institutes.…”
Section: Subjectsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each monkey was extensively trained to perform a fixation task in a mock scanner environment. Detailed descriptions of the surgery and training are provided previously (Harada et al, 2009;Okazawa et al, 2012). All experimental procedures were in accordance with NIH guidelines and were approved by the Animal Experiment Committee of Okazaki National Research Institutes.…”
Section: Subjectsmentioning
confidence: 99%
“…Because the monkeys were overtrained for fixation, the performances during scanning were generally good. The monkey's eye position was continuously recorded using an eye-tracking system based around an infrared CCD camera (60 Hz; Sony), and the task was controlled using custom-made software (Harada et al, 2009;Okazawa et al, 2012).…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…2009). Here, it was shown that DfMRI also reveals the color center using this cognitive subtraction paradigm.…”
Section: Discussionmentioning
confidence: 99%